Effects of fertilization with poultry litter on the cultivation of cherry tomatoes - Solanum lycopersicum L. - Machado, Bruno Belão; Cordeiro, Juliano (Seven Editora, 2023)
Among the vegetables of economic importance, the cherry tomato (Solanum lycopersicum L.) stands out, whose demand has increased over the years, which has caused its cultivation area to have grown. Generally, the cultivation of cherry tomatoes is done conventionally and the use of fertilizers and phytosanitary products during the crop cycle is common. On the other hand, the use of organic fertilization and biofertilizers is constituting a parallel route to reduce and/or replace the chemicals applied. The present study aimed to evaluate the effect of different doses of poultry litter fertilization on cherry tomato production. The experiment was carried out in a greenhouse with the cherry tomato cultivar Solanum lycopersicum cv. Sweet Heaven – Sakata@ and sixth batch poultry bed, with 120 days of fermentation, mixed with maravalha. The experimental design was completely randomized (IHD) with 4 treatments of 10 replications each. The fertilization occurred on two occasions: at planting and 20 days later, according to the treatments: T1 - Control; T2 - 35 g/pot; T3 - 70 g/pot; T4 - 105 g/pot; T5 - 140 g/pot. The data obtained were submitted to analysis of variance and Tukey’s test. For the variables height of the 1st bunch and weight of the bunches, statistical differences were observed between the treatments, which did not occur for the variables number of bunches and fruits/plant and weight of the fruits. The T4 treatment was statistically different from the others in the variable height of the 1st bunch with an average of 57 cm. The same happened for the variable bunch weight, in which T1 presented heavier bunches than the others with an average of 89.1 g/bunch. It was concluded that the use of organic fertilization with poultry litter can be a complementary alternative for the fertilization of tomato crop. DOI:https://doi.org/10.56238/alookdevelopv1-181